(untitled) (International Journal of Management and Sustainability, 2026)
Climate volatility and environmental degradation have increased the pressure for organizational adjustment, especially in resource-based economies like Iraq. Conventional market-based solutions are insufficient for addressing complex ecological issues, necessitating the development of collaborative governance systems that incorporate multi-level stakeholder participation and technological integration. This paper discusses the impact of strategic alliances on environmental recovery outcomes in the Iraqi beverage production industry, examining how different types of alliances can be more effective in ecological adaptation. A quantitative study involving 68 respondents from two Iraqi beverage companies, Al-Waha and Al-Diyar, was conducted. The sampling approach was convenience sampling, targeting organizational members with strategic decision-making authority, including board members and department heads with at least five years of experience in alliance formation, environmental compliance, and operational risk management. The study evaluated four types of alliances, investment, project, marketing, and technical, and five environmental factors: cultural, technological, social, economic, and behavioral, using structured questionnaires organized into dimensions of strategic alliance and environmental adaptation. Structural Equation Modeling was employed to analyze correlations between alliance dimensions and adaptation results. The findings indicated high effectiveness scores across all alliance types, with technical alliances receiving the highest recognition. Similar ratings were observed for environmental adaptation factors. Correlation analysis revealed significant positive relationships between strategic alliances and environmental recovery, with marketing alliances demonstrating the strongest correlation. The study concludes that strategic alliances play a vital role in environmental recovery within the Iraqi manufacturing sector by facilitating access to specialized environmental knowledge, technologies, and stakeholder networks that are often not internalized within individual organizations.